Increased Expression of Interleukin-6 Family Members and Receptors in Urinary Bladder with Cyclophosphamide-Induced Bladder Inflammation in Female Rats - Girard, Beatrice; Cheppudira, Bopaiah P.; Malley, Susan; Schutz, Kristin; May, Victor; Vizzard, Margaret A. (Frontiers in Neuroscience, 2011)
Recent studies suggest that JAK-STAT signaling pathways contribute to increased voiding frequency and referred pain of CYP-induced cystitis in rats. Potential upstream chemical mediator(s) that may be activated by CYP-induced cystitis to stimulate JAK/STAT signaling are not known in detail. In these studies, members of the interleukin (IL)-6 family of cytokines including, leukemia inhibitory factor (LIF), IL-6 and ciliary neurotrophic factor (CNTF) and associated receptors, IL-6 receptor (R) α, LIFR and gp130 were examined in the urinary bladder in control and CYP-treated rats. Cytokine and receptor transcript and protein expression and distribution were determined in urinary bladder after cyclophosphamide (CYP)-induced cystitis using quantitative, real-time polymerase chain reaction (Q-PCR), western blotting and immunohistochemistry. Acute (4 hr; 150 mg/kg; i.p.), intermediate (48 hr; 150 mg/kg; i.p.) or chronic (75 mg/kg; i.p., once every 3 days for 10 days) cystitis was induced in adult, female Wistar rats with CYP treatment. Q-PCR analyses revealed significant (p ≤ 0.01) CYP duration- and tissue- (e.g., urothelium, detrusor) dependent increases in LIF, IL-6, IL-6Rα, LIFR and gp130 mRNA expression. Western blotting demonstrated significant (p ≤ 0.01) increases in IL-6, LIF and gp130 protein expression in whole urinary bladder with CYP treatment. CYP-induced cystitis significantly (p ≤ 0.01) increased LIF-immunoreactivity (IR) in urothelium, detrusor, and suburothelial plexus whereas increased gp130-IR was only observed in urothelium and detrusor. These studies suggest that IL-6 and LIF may be potential upstream chemical mediators that activate JAK/STAT signaling in urinary bladder pathways.